Isolation and SAR studies of bicyclic iminosugars from Castanospermum australe as glycosidase inhibitors. (March 2015) - Kato, Atsushi; Hirokami, Yuki; Kinami, Kyoko; Tsuji, Yutaro; Miyawaki, Shota; Adachi, Isao; Hollinshead, Jackie; Nash, Robert J.; Kiappes, J.L.; Zitzmann, Nicole; Cha, Jin K.; Molyneux, Russell J.; et al.
Graphical abstract: Fourteen iminosugars were isolated from Castanospermum australe . Our side-by-side comparison between bicyclic and corresponding monocyclic iminosugars revealed that inhibition potency and spectrum are clearly changed by their core structures against each enzyme. Highlights: The isolation and structure determination of 14 iminosugars from C. australe . New alkaloid was determined to be 6, 8-di epi -castanospermine. Focus on the difference in the inhibition spectrum of mono- and bi-cyclic iminosugars. Castanospermine (CST) showed stronger anti-hyperglycemia effects than that of miglitol. CST isomers were better α-glucosidase inhibitors than the corresponding piperidines. Abstract: We report the isolation and structural determination of fourteen iminosugars, containing five pyrrolizidines and five indolizidines, from Castanospermum australe . The structure of a new alkaloid was elucidated by spectroscopic methods as 6, 8-di epi -castanospermine (13 ). Our side-by-side comparison between bicyclic and corresponding monocyclic iminosugars revealed that inhibition potency and spectrum against each enzyme are clearly changed by their core structures. Castanospermine (10 ) and 1-deoxynojirimycin (DNJ) have a commond - gluco configuration, and they showed the expected similar inhibition potency and spectrum. In sharp contrast, 6- epi -castanospermine (12 ) and 1-deoxymannojirimycin ( manno -DNJ) both have thed - manno configuration but the α-mannosidase inhibition of 6- epi -castanospermine (12 ) was much better than that of manno -DNJ. 6, 8-Di epi -castanospermine (13 ) could be regarded as a bicyclic derivative of talo -DNJ, but it showed a complete loss of α-galactosidase A inhibition. This behavior against α-galactosidase A is similar to that observed for 1- epi -australine (6 ) and altro -DMDP.